Teacher malaise: risk factors for illness and suffering of teachers as a result of work (Research, Society and Development, 2022)
This article aims to describe the risks of illness and suffering of teachers as a result of their work. The specific objectives are summarized in exposing the teachers' malaise and aggravating the teachers' mental health; score risk factors that corroborate the illness; to present the bibliographic findings of the factors that cause teachers to become ill. To meet the objectives, a narrative review was defined as a methodology, whose premise is to generate new knowledge of the object studied. To tend to the narrative, a description of the problem was made using research published in journals. The results showed that illness is considered a social phenomenon in the western world, triggered by different factors that may be related to physical, chemical, biological, mechanical factors, including social, economic, technological and organizational conditions, which together imply factors considered Psychosocial Risks.